Conflicts, politics and policies of multiple and competitive uses of the mangroves and wetlands resources (2016)
The livelihoods of coastal populations of sub-Saharan Africa depend heavily on access to mangroves and wetland resources. However, with high populations, rapid urban growth and a high dependency, pressures on mangroves and other wetland resources have continued to soar. Thus, there is concern that the long-term values of intact and functioning mangrove ecosystems are not being recognized in current policy decisions, where short-term gains resulting in loss of the ecosystem are being pursued at the expense of long-term sustainability. The connections between mangroves and livelihoods throughout Africa need to be strengthened at the policy level. The policy for multiple and competitive uses of mangroves and wetland resources need to be well developed on the African continent. This is especially true with regards to the potentials of mangroves and wetland resources for aquaculture and ecotourism. It is important to build awareness and political sensitization on mangroves and wetland issues for general development of the continent and its people. This would require strategic planning, followed by policy formulation and programme development. Sustainable multiple usages of mangroves and wetland resources is possible by taking an integrated approach based on solid biological, socio-economic and cultural information.